Udit Keselamatan Jalan (Studi Kasus Jalan Yogyakarta - Bantul Km 8,5 - 10) - Aidil Arisiswanto (Jurusan T.Sipil Fakultas Teknik UMY, 2012)
Udit Keselamatan Jalan (Studi Kasus Jalan Yogyakarta - Bantul Km 8,5 - 10)